1994
DOI: 10.3354/meps110271
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sinking and zooplankton grazing on the release of elements from planktonic debris

Abstract: Laboratory radiotracer experiments compared the effects of zooplankton grazing and microbial decomposition on the release of organic C and Ag, Cd, CO, Pb and PO from phytoplankton cells. After 40 h incubation of diatoms with copepods + microorganisms, 70% of the diatom cellular C was remineralized to CO, (40 Yo), assimilated in copepod tissue (20 %), excreted in fecal pellets (5 %) or released as DOC (5 %), microorganisms alone removed half this amount of diatom C. Copepod grazlng enhanced the conversion of Ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0
1

Year Published

1994
1994
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 41 publications
3
43
0
1
Order By: Relevance
“…fecal pellets, DOC). Microbial release of trace metals from phytoplankton cells and debris has been observed to be a relatively slow process, occurring on a time frame of days to weeks (Frey & Small 1979, Lee & Fisher 1992, even when the microbial community is artificially enriched (Lee & Fisher 1994). Extensive microbial degradation of live plankton cells in the time frame of the crustacean grazing experiments presented here (hours) is unlikely.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…fecal pellets, DOC). Microbial release of trace metals from phytoplankton cells and debris has been observed to be a relatively slow process, occurring on a time frame of days to weeks (Frey & Small 1979, Lee & Fisher 1992, even when the microbial community is artificially enriched (Lee & Fisher 1994). Extensive microbial degradation of live plankton cells in the time frame of the crustacean grazing experiments presented here (hours) is unlikely.…”
Section: Discussionmentioning
confidence: 93%
“…Lee & Fisher (1994) present the results of a similar study in which the release of a suite of mostly nonessential trace metals (Ag, Cd, CO, PO and Pb) from phytoplankton debris was examined in the presence and absence of microorganisms and/or copepods. They concluded that microbial degradation processes can account for the bulk of trace metal regeneration in the ocean, with zooplankton grazing accounting for a fractional enhancement (5 to 15% over a 40 h incubation).…”
Section: Discussionmentioning
confidence: 99%
“…Carbon turnover times measured on the fresh diatom detritus were much shorter than those calculated on natural diatom aggregates in the sea (Smith et al 1992). The short half-time of POC determined by 14 CO 2 release (Lee and Fisher 1994) was attributed to physicochemical leaching, as well as to activities of free enzymes that can temporarily exceed microbial transformation. A substantial release of DOM from 14 C-labeled seston by solubilization was also found by Berman et al (1999) in Lakes Kinneret and Constance.…”
Section: Discussionmentioning
confidence: 99%
“…That zooplankton play an important role in the biogeochemical cycling of metals in marine systems in general is well known, especially regarding particle-reactive metals in the water column Lee and Fisher, 1994;Stewart et al, 2005). Thus, in several studies macro-and meso-zooplankton organisms have been specifically used as biomonitors for assessment of the bioavailability of elements in marine systems, covering a variety of spatial and temporal scales (e.g.…”
Section: Introductionmentioning
confidence: 99%